THE EVALUATION OF CHEMICAL QUALITY OF SUMBAWA WILD HORSE MILK IN DIFFERENT AGES - M. A., Abubakar; Lindawati, S. A.; Hartawan, M. (Jurnal Peternakan Tropika; Vol 5 No 3 (2017), 2017)
Sumbawa Wild Horse Milk is one of the pure milk that is milking from a horse farmed by farmer in Sumbawa Island. This research aimed to know the chemical quality of wild horse milk in Sumbawa in the age of the horse 3, 5 and 7 years old. This study was conducted in two places. The sampling was conducted in Moyo Hilir subdistrict, Sumbawa Regency and the chemical quality evaluation was conducted in Livestock Production Technology of Laboratory and Microbiology, Faculty of Animal Husbandry Udayana University. The design that used in this study was Randomized Complete Design (RAD) with 3 treatments and 3 repetitions to obtain 9 unit of experiments. The variables that observed in this study were fat content, lactose, protein, pH and total of microbes. The results showed that the fat content in the age of 3 is 2.17%, lactose 2.61%, protein 2.41%, pH 5.50% and total of bacteria 5.5x10 7 cfu/ml. In the 5 years old of Sumbawa wild horse milk containes 2.94% of fat, 2.19% of lactose, 2.04% of protein, pH value 5.50 and total bacteria of 5.50 cu / ml. In the wild horse milk age 7 years of 3.67% fat, 1.79% lactose, 2.80% protein, 5.87 pH value and total of bacteria 1.70x10 6 cfu/ml. Based on the result that obtained, can be concluded that the fat, lactose, protein and pH value of Sumbawa wild horse milk at age 3, 5 and 7 years already met the Indonesian National Standard, but based on the results of total of bacteria, it is unfit consumption seen from total of bacteria exceeds the normal threshold of SNI.                                             Keywords: sumbawa wild horse milk, chemical quality, age